Gênero, velhice e geração: a violência familiar contra a mulher idosa em Vitória (ES), 2010-2012 - Silveira, Luciana (2015)
This work intends to analyze domestic violence against the elderly woman, especially practiced by children and grandchildren, in the city of Vitória (ES), as an expression of social constructions about the genre and of old age and intergenerational relations. To do so, were used as sources of police reports recorded by the Station of Care and Protection to the Elderly Person (DAPPI), located in Vitória (ES), in their first two years of existence, December 2010 to December 2012. From the transcript of the data present in the police report DAPPI sought to retrieve the socio-demographic profile of the victims and authors as well as the motivations presented in the report of the fact. Despite the presence of structural factors, such as alcohol and drug addiction, in the cases analysed, it is believed that violence against older women must be understood, especially, from the categories of gender and generations. Thus, older women are victims, firstly, built and inequalities perpetrated by patriarchy, which tend to put the man in a position of power in relation to the woman. And it is important to highlight a relationship of power not just of the spouse in relation to the wife or father in relation to daughters, but also the children and grandchildren regarding the mother or grandmother. With a view to the maintenance of the social roles of dominationsubmission patriarchy legitimizes violence against women. In addition, older women are victims of generational inequalities, producing a hierarchy similar to present gender relations with regard to age. Finally, there is the building of a negative image of old age, which associates the poorness, decadence, dependence and fragility. This image enhances vulnerability to violence experienced by women throughout her life.